Introductory biochemistry for engineering and technology - Zarina Zakaria; Singh, Harbant (Penerbit Universiti Malaysia Perlis, 2015)
This textbook introduces to the students the basic concepts of chemistry viewed from the prospective of biology. It focuses on the engineering and technical point of view since this science has a broad spectrum coverage sretching across medical, industrial, agricultural and other disciplines of science.